Profitability Evaluation of Load-Following Nuclear Units with Physics-Induced Operational Constraints. (2nd December 2017) - Ponciroli, R.; Wang, Y.; Zhou, Z.; Botterud, A.; Jenkins, J.; Vilim, R. B.; Ganda, F.
Abstract: This work explores the technical challenges associated with flexible operation for nuclear power plants (NPPs) and evaluates whether a flexible operational mode could improve the profitability of nuclear units by allowing nuclear plant owners/operators to reduce output when prices are low and instead shift capacity to the ancillary services markets. As compared to conventional power plants, NPP flexible operation capabilities are affected by additional physics-induced constraints. Among the most limiting constraints is the negative reactivity insertion following every reactor power drop due to the increased concentration of xenon, a strong neutron poison. In this work, a previously available power system operation model based on mixed-integer linear programming optimization was improved by implementing a dedicated representation of these physics-induced constraints for pressurized water reactors (PWRs). Because the xenon-related constraint involves nonlinear governing dynamics, a dedicated parametric approach was implemented. To evaluate the economic implications of flexible PWR operation, a case study using realistic power system data representative of the southwestern United States was analyzed. The results indicate that flexible operation can increase the revenue of nuclear units while at the same time reducing total electric system operating costs.